High-Normal Serum Magnesium and Hypermagnesemia Are Associated With Increased 30-Day In-Hospital Mortality: A Retrospective Cohort Study - Tan, Liao; Xu, Qian; Li, Chan; Liu, Jie; Shi, Ruizheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Magnesium, the fourth most abundant mineral nutrient in our body, plays a critical role in regulating ion channels and energy generation, intracardiac conduction, and myocardial contraction. In this study, we assessed the association of admission serum magnesium level with all-cause in-hospital mortality in critically ill patients with acute myocardial infarction (AMI). Methods: Clinical data were extracted from the eICU Collaborative Research Database (eICU-CRD). Only the data for the first intensive care unit (ICU) admission of each patient were used and baseline data were extracted within 24 hours after ICU admission. Logistic regression, cox regression, and subgroup analyses were conducted to determine the relationship between admission serum magnesium level and 30-day in-hospital mortality in ICU patients with AMI. Results: A total of 9005 eligible patients were included. In the logistic regression analysis, serum magnesium in 2.2 to ≤ 2.4 mg/dL and >2.4 mg/dl levels were both significant predictors of all-cause in-hospital mortality in AMI patients. Moreover, serum magnesium in 2.2 to ≤ 2.4 mg/dL showed higher risk of in-hospital mortality than magnesium in >2.4 mg/dl (adjusted odds ratio, 1.63 versus 1.39). The cox regression analysis yielded similar results (adjusted hazard ratio, 1.36 versus 1.25). Conclusions: High-normal serum magesium and hypermagnesemia may be useful and easier predictors for 30-day in-hospital mortality in critical ill patients with AMI.